The Effect of Chronic Alprazolam Intake on Memory, Attention, and Psychomotor Performance in Healthy Human Male Volunteers - Chowdhury, Zahid Sadek (Behav Neurol, 2016)
Alprazolam is used as an anxiolytic drug for generalized anxiety disorder and it has been reported to produce sedation and anterograde amnesia. In the current study, we randomly divided 26 healthy male volunteers into two groups: one group taking alprazolam 0.5 mg and the other taking placebo daily for two weeks. We utilized the Cambridge Neuropsychological Test Automated Battery (CANTAB) software to assess the chronic effect of alprazolam. We selected Paired Associates Learning (PAL) and Delayed Matching to Sample (DMS) tests for memory, Rapid Visual Information Processing (RVP) for attention, and Choice Reaction Time (CRT) for psychomotor performance twice: before starting the treatment and after the completion of the treatment. We found statistically significant impairment of visual memory in one parameter of PAL and three parameters of DMS in alprazolam group. The PAL mean trial to success and total correct matching in 0-second delay, 4-second delay, and all delay situation of DMS were impaired in alprazolam group. RVP total hits after two weeks of alprazolam treatment were improved in alprazolam group. But such differences were not observed in placebo group. In our study, we found that chronic administration of alprazolam affects memory but attentive and psychomotor performance remained unaffected.